2014
DOI: 10.1016/j.ygyno.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory investigation of links between changes in adipokines and quality of life in individuals undergoing weight loss interventions: Possible implications for cancer research

Abstract: OBJECTIVE Obesity has been linked to a wide spectrum of malignancies, with the strongest association demonstrated for endometrial cancer. Although the mechanisms are not yet entirely clear, a number of risk biomarkers have been proposed, including altered adipokines. Systemic levels of these adipose derived molecules have also been linked in prior research to self-reported quality of life (QOL). They study objective was to examine the hypothesis that adipokine changes during intentional weight loss may be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“… Linkov et al (2014 ) 25 demonstrated that the weight loss was associated not only with better quality of life, but also with decrease in adipokines; they also demonstrated a correlation between the level adipokines reduction and improvement of the physical quality of life 25 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… Linkov et al (2014 ) 25 demonstrated that the weight loss was associated not only with better quality of life, but also with decrease in adipokines; they also demonstrated a correlation between the level adipokines reduction and improvement of the physical quality of life 25 .…”
Section: Discussionmentioning
confidence: 96%
“…Overload or repetitive use may result in tendon disease and seems to be the dominant factor initiating the inflammatory response. It is believed that some of the damage caused by the overload is mediated through inflammatory process 2 , 25 , 33 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Para finalizar, Catalán y col 1 apuntan que la adiposidad tras la CB presenta una trayectoria diferente a las del IMC y el peso corporal, pudiendo influir en la evolución de algunas variables bioquímicas. Esto lleva a los autores a plantearse nuevas hipótesis, como que los cambios en la adiposidad corporal producen cambios en las hormonas producidas por el tejido adiposo o en otras variables metabólicas que se han asociado con la mejora en la calidad de vida tras la pérdida de peso 11 . Nos parece interesante esta nueva propuesta de los autores; pero aunque el IMC se considere una medida indirecta de la adiposidad sujeto a una elevada tasa de error 12 , actualmente las recomendaciones sobre los indicadores de éxito de la CB son en función de la disminución del peso, siendo los más utilizados el porcentaje de sobrepeso perdido (PSP) y el PEIMCP, siendo este último el más recomendado 13 .…”
Section: Sr Directorunclassified
“…Sin embargo, a pesar de que si no se dispone de una cuantificación de la evolución del porcentaje de grasa corporal, que es lo que define la obesidad, el IMC es la herramienta epidemiológica utilizada con mayor frecuencia, dicha medida no es más que un indicador indirecto de la adiposidad sujeto a una elevada tasa de error 3,10 . En este sentido, nuestro grupo ha mostrado recientemente que la adiposidad tras la cirugía bariátrica presenta una trayectoria diferente al IMC y al peso corporal, pudiendo influir en la evolución de algunas variables bioquímicas tras la cirugía bariátrica, por ejemplo el perfil lipídico 11 . Podría plantearse la hipótesis de que los cambios en la adiposidad corporal producen cambios en las hormonas producidas por el tejido adiposo (adipoquinas) como leptina y adiponectina u otras variables metabólicas, que se han asociado con la mejora en la calidad de vida tras la pérdida de peso 12 .…”
unclassified
“…A correlation between quality-of-life measures and leptin was found which may help to further understand its role in weight regulation; ultimately, the understanding of this role could guide new drug development and finally support weight loss and weight-associated diseases such as cancer (Linkov et al, 2014). In a recent study, exploratory aspects were added to a weight-loss intervention, and several adipokines and other metabolically relevant parameters were measured.…”
mentioning
confidence: 99%